Implementasi Pendekatan Konstruktivisme pada Pembelajaran Cerita Fantasi dengan Kurikulum Merdeka di Kelas VII SMPN 1 Jenangan - Kenang Ageng Jati; Teguh Suharto; Dwi Rohman Soleh (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
This study aims to describe the implementation of learning clearly about the implementation of the constructivist approach to the independent curriculum in class VII SMPN 1 Jangan, Ponorogo.The research method used in this study was a qualitative approach with the data source in this study being class VII teachers at SMPN 1 Jangan, Ponorogo. This study used data collection techniques in the form of data collection techniques used in this study were observation, interview and documentation methods. The main instruments in descriptive qualitative research are researchers using tools in the form of observation guidelines and interviews. The data analysis used is Miles and Huberman's interactive model, namely data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses the triangulation method by comparing the results of observations, interviews, and documentation.The results showed that when learning a constructivist approach to learning fantasy stories with an independent curriculum in class VII SMPN 1 Jangan. Goes well. The existence of cooperation between teachers and students makes learning objectives compatible with the objectives.